Música na dor do recém-nascido a termo submetido à punção venosa: ensaio clínico randomizado - Melo, Gleicia Martins (2018)
Among the non-pharmacological measures to minimize physiologic and behavioral reactions on newborns exposed to pain, one has music. The objective was to assess the effect of music intervention when applied in two time extensions on bio-behavioral responses of pain in full-term newborns before, during and after the venipuncture for blood collection. A randomized clinical trial carried out in a philanthropic hospital, situated in Fortaleza/Ceará/Brazil from February/December/2017. The sample consisted of 52 full-term newborns hospitalized in Rooming-in, being 13 randomized on each group: Music Group 1 (MG1); Music Group 2 (MG2); Control Group 1 (CG1) and Control Group 2 (CG2). Two lullaby songs from the collection Music Baby: Bonne Nuit were played in 40 decibels, by MP3 and earphones on MG1 and on MG2, for 10 and 15 minutes before, during (whilst the painful procedure lasts) and two minutes after. The CG1 (without music, for 10 minutes) and CG2 (without music, for 15 minutes) also used earphones. The newborns participating were videotaped to get facial reactions and heart rate (HR) (Polar RS 200). The measured variables were facial mimic from the Neonatal Facing Coding Scale (NFCS) crying, HR. Data collect was carried out in five moments using NFCS: Basal (BM - 20 initial seconds - without handling), Pre-procedure 1 (PPM1 - 20 initial and final seconds, each), Pre-procedure 2 (PPM2 - vein search time), Procedure (PM - antisepsis, puncture, squeezing/blood aspiration and compression time) and Recovery (RM - 20 initial and final seconds after end of compression); five moments for crying and HR: BM (2 minutes), PPM1(2 initial and final minutes), PPM2 (vein search time), PM (antisepsis, puncture, squeezing/blood aspiration and compression time) and RM (2 minutes). Project approved by the Research and Ethics Committee of the institution. As for the neonatal variables (categorical and numeric), there were significant statistics between allocation groups only for the therapeutic variable (puncture site) (p = 0.003). Pearson Qui-Square Test showed that, the percentage of facial mimic absence (brow bulge, narrow eyes, deepened nasolabial furrow, horizontal opened mouth, taut tongue) was significantly higher on MG2, when compared to the other groups, in all moments analyzed (p< 0.05). This shows that the expression of pain was lower in MG2. The crying had more presence in antisepsis, puncture, squeezing/blood aspiration on MG1, CG1 and CG2, as well as in compression, on CG1 and CG2. On PPM1 (initial), on MG1, and in other moments, on MG2, the newborns showed higher absence of crying (Pearson Qui-Square Test), with p<0.05. MG2 showed HR mean lower than neonates did from other groups from BM until RM, with significance (p=0.000) on BM, PPM1, PPM2, PM (antisepsis, squeezing/blood aspiration) and RM (ANOVA). It concludes that music administered for 15 minutes, on reduction of pain bio-behavioral responses in newborns submitted to venipuncture for blood collect, showed better results to the effect obtained in music administration for 10 minutes, confirming the hypothesis of the study.